Effect of Mindfulness-Based Self-Care Education on the Quality of Female Nurses’ Life - Mahdieh Fallah; Maasoumeh Barkhordari-Sharifabad; Khadijeh Nasiriani (مراقبت پرستاری و مامایی ابن سینا, 2022)
Background and Objective: The stressful nature of nursing can affect the quality of nurses’ life. Mindfulness-based stress reduction can help improve the quality of their life. Therefore, the present study was conducted to investigate the effect of mindfulness-based self-care education on the quality of female nurses’ life working in Afshar Hospital, Yazd, Iran. Materials and Methods: This experimental study was conducted in 2020 on 60 female nurses working in Afshar Hospital (Yazd, Iran) randomly divided into experimental and control groups. For the experimental group, mindfulness-based self-care was taught in eight two-hour sessions. On the other hand, the control group did not receive any intervention. Data collection tools included a demographic questionnaire and the World Health Organization’s Quality of Life questionnaire. Data were analyzed using descriptive and inferential statistics with a significance level of 0.05 using the SPSS software (version 19). Results: The mean quality of life score before the intervention was not significantly different (P=0.11) between the control (69.58±13.00) and the experimental (64.58±11.41) group. After the intervention, the mean was 68.75±14.21 and 69.58±09.09 in the control and experimental group, respectively; however, the difference was not significant (P=0.78). Regarding the dimensions of the quality of life, there was a significant difference only in the psychological dimension (P=0.001). Conclusion: Mindfulness-based self-care education affects the psychological dimension of the nurses’ quality of life; therefore, it is suggested that programs of this kind be implemented for nurses in this field periodically to improve the quality of their life.